The heritage crusade and the spoils of history - Lowenthal, David (Cambridge, U.K. ; New York : Cambridge University Press, 1998)
"Heritage has burgeoned over the past quarter of a century from a small elite preoccupation into a major popular crusade. Everything from Disneyland to the Holocaust Museum, from the Balkan wars to the Northern Irish Troubles, from Elvis memorabilia to the Elgin Marbles bears the marks of the cult of heritage. In this acclaimed book David Lowenthal explains the rise of this new obsession with the past and examines its power for both good and evil."--Jacket.
1. Heritage Ascendent 2. Personal Legacies 3. Collective Legacies 4. Heritage Assailed 5. The Purpose and Practice of History 6. The Purpose of Heritage 7. The Practice of Heritage 8. Being First 9. Being Innate 10. Rivalry and Restitution.
Originally published: Possessed by the past. New York : Free Press, c1996.
Includes bibliographical references (p. 293-314) and index.
Keywords: History -- Philosophy